Awangarda : tradition and modernity in postwar Polish music - Vest, Lisa Cooper (California studies in 20th-century music ;, 2021)
"In Awangarda, Lisa Cooper Vest explores how the Polish postwar musical avant-garde stood in stark contrast to its Western European counterparts. Rather than representing a rejection of the past, the Polish avant-garde movement emerged as a manifestation of national cultural traditions stretching back into the interwar years and even earlier, into the nineteenth century. Polish composers, scholars, and political leaders wielded the promise of national progress to broker consensus across generational and ideological divides. Together, they established an avant-garde musical tradition that pushed against the limitations of strict chronological time and instrumentalized discourses of backwardness and forwardness to articulate a Polish road to modernity. This is a history that resists Cold War periodization, opening up new ways of thinking about nations and nationalism in the second half of the twentieth century"--